^{c}. ( y

^{c}+ y))) . y = y

I have,

(x + (x

^{c}. ( y

^{c}+ y))) . y =

(x + (x

^{c}. 1)) . y

= (x + x

^{c}) . y

= 1 . y

= y

Is this correct?

Thanks

Tony

I need to prove, (x + (x^{c} . ( y^{c} + y))) . y = y

I have,

(x + (x^{c} . ( y^{c} + y))) . y =

(x + (x^{c} . 1)) . y

= (x + x^{c}) . y

= 1 . y

= y

Is this correct?

Thanks

Tony

I have,

(x + (x

(x + (x

= (x + x

= 1 . y

= y

Is this correct?

Thanks

Tony

- maggiemagnet
**Posts:**354**Joined:**Mon Dec 08, 2008 12:32 am-
**Contact:**

Looks good to me!